2023
DOI: 10.1007/s40120-023-00521-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Eptinezumab in Episodic and Chronic Migraine Headache in the UAE: A Retrospective Study

Abstract: Introduction Eptinezumab is a humanized IgG1 immunoglobulin monoclonal antibody administered intravenously as a preventative migraine treatment. Previously conducted randomized, double-blind, placebo-controlled trials exhibited significant reductions in monthly migraine frequency among adults experiencing episodic and chronic migraine. The present study seeks to expand upon the current findings and to evaluate eptinezumab’s efficacy as a preventative treatment for chronic and episodic migraine pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Remarkably, this study demonstrated that patients experiencing continued migraine burden who had previously tried other anti-CGRP mAb preventive treatments responded positively to eptinezumab; this suggests empirically that exposure and trial of one anti-CGRP mAb does not necessarily preclude a positive response to eptinezumab treatment. Recent studies also corroborate this finding [22][23][24][25], with one study showing that patients with previous exposure to erenumab or galcanezumab who subsequently initiated eptinezumab treatment had an overall reduction in monthly migraine days of ∼ 8.4 and ∼ 8.2, respectively, over a 6-month period [22]. These findings have implications for public health and best practices for clinicians navigating through treatment decisions among a variety of advanced migraine therapies.…”
Section: Discussionmentioning
confidence: 72%
“…Remarkably, this study demonstrated that patients experiencing continued migraine burden who had previously tried other anti-CGRP mAb preventive treatments responded positively to eptinezumab; this suggests empirically that exposure and trial of one anti-CGRP mAb does not necessarily preclude a positive response to eptinezumab treatment. Recent studies also corroborate this finding [22][23][24][25], with one study showing that patients with previous exposure to erenumab or galcanezumab who subsequently initiated eptinezumab treatment had an overall reduction in monthly migraine days of ∼ 8.4 and ∼ 8.2, respectively, over a 6-month period [22]. These findings have implications for public health and best practices for clinicians navigating through treatment decisions among a variety of advanced migraine therapies.…”
Section: Discussionmentioning
confidence: 72%
“…They found a significant difference in MMD after three months for patients who were naïve and for patients who were previously treated with erenumab or galcanezumab in (mean MMD after three months (SD): naïve: 2.13 (1.86); erenumab: 5.69 (5.96); galcanezumab: 7.47 (6.77), respectively; p < 0.001). After dosage increase from 100 to 300mg in 14 patients, MMD did not differ after six months (mean MMD after six months (SD): naïve: 3.25 (4.27); erenumab: 3.63 (4.86); galcanezumab: 3.82 (2.67)) [ 9 ]. The responder rates after 3 months were better than in our cohort, but after six months a remarkable better response was seen.…”
Section: Discussionmentioning
confidence: 99%
“…This is the only drug used as an intravenous infusion, thus offering pharmacokinetic advantages over mAbs used subcutaneously. 124 6. 3 reported to relieve pain within 2 h and greatly reduce the frequency of migraine attacks.…”
Section: Migraine Drugs and Their Synthesismentioning
confidence: 99%
“…This is the only drug used as an intravenous infusion, thus offering pharmacokinetic advantages over mAbs used subcutaneously. 124 6.3.2. Gepants.…”
Section: Migraine Drugs and Their Synthesismentioning
confidence: 99%
See 1 more Smart Citation